Observations, Meteorites, and Models: A Preflight Assessment of the Composition and Formation of (16) Psyche. Issue 3 (25th March 2020) - Elkins‐Tanton, L. T.; Asphaug, E.; Bell, J. F.; Bercovici, H.; Bills, B.; Binzel, R.; Bottke, W. F.; Dibb, S.; Lawrence, D. J.; Marchi, S.; McCoy, T. J.; Oran, R.; et al.
Abstract: Some years ago, the consensus was that asteroid (16) Psyche was almost entirely metal. New data on density, radar properties, and spectral signatures indicate that the asteroid is something perhaps even more enigmatic: a mixed metal and silicate world. Here we combine observations of Psyche with data from meteorites and models for planetesimal formation to produce the best current hypotheses for Psyche's properties and provenance. Psyche's bulk density appears to be between 3, 400 and 4, 100 kg m −3 . Psyche is thus predicted to have between 30 and 60 vol% metal, with the remainder likely low‐iron silicate rock and not more than 20% porosity. Though their density is similar, mesosiderites are an unlikely analog to bulk Psyche because mesosiderites have far more iron‐rich silicates than Psyche appears to have. CB chondrites match both Psyche's density and spectral properties, as can some pallasites, although typical pallasitic olivine contains too much iron to be consistent with the reflectance spectra. Final answers, as well as resolution of contradictions in the data set of Psyche physical properties, for example, the thermal inertia measurements, may not be resolved until the NASA Psyche mission arrives in orbit at the asteroid. Despite the range of compositions and formation processes for Psyche allowed by the current data, the science payload of the Psyche mission (magnetometers, multispectral imagers, neutron spectrometer, and a gamma‐ray spectrometer) will produce data sets that distinguish among the models. Plain Language Summary: Since the NASA mission to asteroid (16) Psyche was selected, interest from the public and from the scientific community in the asteroid has risen considerably. New observations of the asteroid's physical properties indicate a different composition than earlier data had shown. A decade ago, much of the community thought the asteroid was 90% metal on its surface. There are still contradictions in the compilation of all current data, but the best analysis indicates that Psyche's density is between 3, 400 and 4, 100 kg m −3, indicating it is a mixture of rock with between 30 and 60 vol% metal. Key Points: New observations of asteroid (16) Psyche's physical properties indicate a different composition and properties than earlier data had shown The best current analysis indicates that Psyche's density is 3, 400‐4, 100 kg m ‐3, indicating a mixture of rock with 30‐60 vol% metal Contradictions in data of Psyche physical properties may not be resolved until the NASA Psyche mission arrives at the asteroid